PROPOSITION IN PRAGMLINGUISTICS (Proceedings of International Educators Conference, 2023)
This paper is devoted to the study of proposition in linguistics and pragmatics. We will analyze definitions of proposition given by different linguists and analyze them. Based on them, at the end of this work, we will give conclusions on the role of proposition in pragmalinguistcs.